Analisis Kemampuan Berpikir Kreatif Mahasiswa PGSD dalam Mata Kuliah Inovasi Pembelajaran melalui Penerapan Model Project Based Learning (PjBL) - Ade Bagus Primadoni; Rachmat Imam Muslim (Universitas Islam Nahdlatul Ulama Jepara, 2026)
This study was motivated by the importance of creative thinking skills as one of the essential competencies in the 21st century that should be developed through higher education learning processes. One learning model that has the potential to facilitate the development of creative thinking skills is Project-Based Learning (PjBL). This study aimed to analyze the creative thinking skills of students in the Elementary School Teacher Education Program (Pendidikan Guru Sekolah Dasar / PGSD) in the Learning Innovation course through the implementation of the PjBL model. The study employed a quantitative descriptive method supported by qualitative data. The participants consisted of 30 fifth-semester PGSD students at Muhammadiyah University of Kendal Batang selected using a saturated sampling technique. Data were collected through questionnaires, observations, and interviews. Data analysis was conducted descriptively to describe students' creative thinking skills based on the indicators of fluency, flexibility, and originality. The findings revealed that students' creative thinking skills improved across all indicators after the implementation of PjBL. The percentage of fluency skills increased from 65.63% to 82.50%, flexibility from 61.56% to 78.44%, and originality from 61.67% to 82.08%. The highest improvement was found in the originality indicator, with an increase of 20.41%. Observation and interview results indicated that project-based learning provided students with opportunities to engage in discussions, exchange ideas, receive feedback, and reflect on and revise the projects they developed. These findings suggest that the implementation of PjBL is associated with a tendency to improve students' creative thinking skills during the learning process.